Cameron's cave-in on plain packaging is a boost to industry - Daube, Mike; Chapman, S. (British Medical Journal, 2013)
Australia has shown that governments can act on plain packaging of tobacco products. The UK government would do well to reflect on its responsibility for the deaths and suffering it could have prevented but didn’t.